Mídias audiovisuais de entretenimento como estratégia de contextualização problematizadora para o ensino de ciências - Lovato, Fabricio Luís (2019)
Science teaching in schools should enable students to appropriate the structure of scientific knowledge and its explanatory and transformative potential, in order to develop a comprehensive look at the world. However, assessment results show that it has not been able to motivate students properly, with disastrous consequences. The limitations and weaknesses observed in science education point to the need for teachers in the area to adopt new ways of teaching. To this end, several strategies have been studied in order to achieve learning, among them the “active learning methodologies”. These methodologies, by allowing students greater protagonism and involvement in building their knowledge, improve student performance compared to purely expository classes at all levels of education. Communication between equals acquires more importance, involving the exchange of information, joint participation in activities and the resolution of challenges. In addition, one should also seek to relate the situations present in the daily life of students as well as their interests with scientific knowledge. The “audiovisual entertainment media” are remarkably present elements in childhood and adolescence. This expression refers to programations assisted in leisure time, which combine image and sound, being broadcast in media such as television or the computer. This category includes movies, series, cartoons, soap operas, game shows, talk shows, documentaries, among others. Thus, the objective of this work was to investigate how these various media can be used as tools to contextualize and problematize science teaching, actively involving students in the teaching-learning process. From a literature review on active learning methodologies and an analysis on the presence and use of “audiovisual entertainment media” in textbooks and ENEM tests, didactic sequences were prepared, applied and analyzed involving the following media: cartoon, culinary competition program, science fiction movie and criminal investigation series. The contents of Sciences/Biology in which the didactic sequences were implemented were: Environmental Education; Cytology; Anatomy and Physiology; and Genetics. A total of 117 students from four different classes and two schools participated in the research. The active methodologies used involved readings, discussions/argumentations, experiments, simulations, model constructions and visual and textual productions. A Genetics question book based on a series of science fiction movies was also produced. The inclusion of the formats, characters, plots and contexts of these media, employed with the active participation of students, attracted their attention, curiosity and motivation, allowed for a better understanding and assimilation of the themes taught and positively impacted relationships with peers and teachers, allowing thus work on conceptual, procedural and attitudinal contents.